Circulating BiP/Grp78 is a novel prognostic marker for sepsis‐mediated immune cell death. (17th September 2020) - Doerflinger, Marcel; Reljic, Boris; Menassa, Joseph; Nedeva, Christina; Jose, Irvin; Faou, Pierre; Mackiewicz, Liana; Mansell, Ashley; Pellegrini, Marc; Hotchkiss, Richard; Puthalakath, Hamsa
Abstract : Sepsis remains to be a major contributor to mortality in ICUs, and immune suppression caused by immune cell apoptosis determines the overall patient survival. However, diagnosis of sepsis‐induced lymphopenia remains problematic with no accurate prognostic techniques or biomarkers for cell death available. Developing reliable prognostic tools for sepsis‐mediated cell death is not only important for identifying patients at increased risk of immune suppression but also to monitor treatment progress of currently trialed immunotherapy strategies. We have previously shown an important role for endoplasmic reticulum stress (ER stress) in inducing sepsis‐mediated cell death and here report on the identification of a secreted form of the ER chaperone BiP (immunoglobulin binding protein) as a novel circulating prognostic biomarker for immune cell death and ER stress during sepsis. Using biochemical purification and mass spectrometry coupled with an established in vitro sepsis cell death assay, we identified BiP/Grp78 as a factor secreted by lipopolysaccharide‐activated macrophages that is capable of inducing cell death in target cells. Quantitative ELISA analysis showed significantly elevated levels of circulating BiP in mice undergoing polymicrobial sepsis, which was absent in Bim −/− mice that are protected from sepsis‐induced lymphopenia. Using blood serum from human sepsis patients, we could detect a significant difference in levels of secreted BiP in sepsis patients compared to nonseptic controls, suggesting that secreted circulating BiP could indeed be used as a prognostic marker that is directly correlative to immune cell death during sepsis. Abstract : Death of immune cells is a significant contributor to the pathology of polymicrobial sepsis. Diagnosis of sepsis‐induced lymphophenia is currently challenged by a lack of accurate biomarkers for the condition. Here, Hamsa Puthalakath and co‐authors report that lipopolysaccharide‐activated macrophages release the ER chaperone BiP (binding immunoglobin protein, also known as GRP78) into the extracellular milieu. This secreted form of BiP binds target cells through an unknown receptor and induces ER stress, resulting in apoptosis. Secreted circulating BiP could be used as a prognostic marker for immune cell death during sepsis.